Advanced device for measuring linear and angular components of small displacements of monitor object surfaces - Igor P. Miroshnichenko (Advanced Engineering Research, 2017)
Introduction. Measuring the linear and angular components of small displacements of the monitor object surfaces is considered. A high-precision non-contact device based on the advanced laser technologies and methods of optical interferometry, namely a double-pass laser interferometer with integrated branches, is developed to perform these measurements. The calculated and experimental validation of the device is offered. Thus, the quality and condition of the materials and products can be controlled by means of the acoustic non-destructive methods. Materials and Methods. New software and mathematical models describing optical fields of the interference patterns generated by the interferometer under consideration are offered. Various types of beam splitters and cases of polarization are used under the numerical simulation of the intensity distributions in the interference patterns. Research Results. New mathematical models and software for the numerical simulation of the optical radiation intensity fields in the interference patterns considering both linear and angular components of small displacement of the surface of the test object are developed. A new interference technique of measuring small linear and angular displacements is developed and theoretically grounded. It allows combining the meter measuring capabilities for both small linear and angular displacements of the monitor object surfaces in a single tool. New optical interference methods and means for the noncontact measurements of small linear and angular movements of the monitor object surfaces that implement the method capabilities and extend the functionality of the known indicators of small displacements are offered. Discussion and Conclusions. The obtained results can be used for the high-precision measurements of small linear and angular displacements of surfaces of the objects under control. Areas of application are the following: experimental research; assessment and diagnostics of the structural materials samples; investigations of fast wave processes in the layered structures of complex shape made of the anisotropic composite materials. The methods developed in this study are applicable in such industries as mechanical engineering, shipbuilding, aircraft engineering, instrument making, power engineering, and etc.